Enhancing food security amid climate change: assessing impacts and developing adaptive strategies - Bornwell Mutale; Shouhan Dai; Ziqi Chen; Sahya Maulu (Cogent Food & Agriculture)
Climate change poses significant challenges to global food security, impacting food availability, accessibility, utilization, and stability. This paper employs a narrative review approach to provide a comprehensive analysis of the complex interactions between climate change and food security, highlighting key strategies for enhancing resilience amid climate change. Drawing on interdisciplinary research, we outline strategies to bolster agricultural productivity, improve market access, promote sustainable food production, and foster water-energy-food cross-sectoral collaboration. We emphasize the importance of addressing socio-economic disparities and geopolitical dynamics in food security efforts. Furthermore, we highlight the necessity for inclusive decision-making processes that prioritize the needs of vulnerable communities. While existing strategies offer a framework for addressing current challenges, future research should focus on refining adaptation measures, enhancing predictive modeling, and evaluating long-term effectiveness. Innovations in technology, policy, and governance hold promise for building more resilient, equitable, and sustainable food systems that can withstand the challenges of climate change and ensure food security for all.